ANALISIS KEPUASAN PELAYANAN OBAT PADA PASIEN DI PUSKESMAS BERSTANDAR ISO 9001:2008 DI DONGGALA KECAMATAN BANAWA - Sri Ayu Noviyanti; Alwiyah Mukaddas; Muhamad Rinaldhi Tandah (As-Syifaa Jurnal Farmasi, 2017)
Community health center is technical implementation unit of a district / municipality health service who are responsible for organizing health development in a working area. The aims of this study is to determine the relationship between drug services with the level of patient satisfaction at the pharmacy unit of Donggala community health center in Banawa subdistrict, and also to know the level of  patient satisfaction and expectations by measuring with Importance Performance Analysis method to the five dimensions of service in the pharmacy unit at Donggala community health center of Banawa subdistrict. This research was conducted at the pharmacy unit of Donggala community health center in Banawa subdistrict on September 2016 until December 2016 by purposive sampling using questionnaire as instrument through Likert scale. Patient satisfaction are measured using 5 dimension of service which are tangible, relibility, responsiveness, assurance and empathy were analyzed by Importance Performance Analysis (IPA). As the result with 151 respondents at the average of gap (GAP) is -0.82 and 80.87% match rate and the most widely indicator were mapped by cartesius diagram is in quadrant A which are the quality service must still be considered and improved. This is also shows patient in Donggala community health center are still less satisfied and their expectation are still below.